Annual report 2007 FKKKSA - Universiti Teknologi Malaysia, Fakulti Kejuruteraan Kimia (Faculty of Chemical & Natural Resources Engineering, 2008)
This report was published annually to review the faculty's achievements in academic programmes as well as research and innovation throughout the year. This report also summarized other important events that involved students, academicians, and staff, etc.